Immediate discontinuation of ablation during pulmonary vein isolation remarkably decreases the incidence of esophageal thermal lesions even when using steerable sheaths. Issue 1 (3rd June 2016) - Watanabe, Norikazu; Chiba, Yuta; Onishi, Yoshimi; Kawasaki, Shiro; Munetsugu, Yumi; Onuma, Yoshimasa; Itou, Hiroyuki; Onuki, Tatsuya; Minoura, Yoshino; Adachi, Taro; Kawamura, Mitsuharu; Asano, Taku; et al.
Abstract: Background: Left atrial–esophageal fistulas (LAEFs) are serious complications with high mortality after atrial fibrillation radiofrequency ablation (AFRA). Decreasing the incidence of esophageal thermal lesions (EsoTLs) that may lead to LAEFs is important. The aim of this study was to suppress EsoTL development and determine the appropriate alarm setting for a temperature‐monitoring probe by using steerable sheath (STS) methods. Methods: We enrolled 82 consecutive patients (mean, 61.9±11.7 years; 75.6% men) who underwent AFRA, including pulmonary vein isolation for symptomatic, drug‐refractory atrial fibrillation with esophageal temperature monitoring by using STS between January 2011 and April 2014. All patients underwent upper gastrointestinal endoscopy (UGE) 1–3 days after AFRA. The timing of ablation discontinuation in the first 17 patients was determined by each physician during AFRA (only monitoring group, OM). In the next 65 patients, physicians were to immediately discontinue ablation when an alarm set at 39 °C went off (instruction group, INS). We compared two groups with respect to the incidence of EsoTLs. Results: Among the 82 patients, 5 (6.1%) had EsoTLs after AFRA. EsoTLs occurred in 3 of 17 patients (17.6%) and 2 of 65 patients (3.1%) in the OM and INS groups, respectively. The incidence of EsoTLs in the INS group was significantly lower than that in the OM group ( p =0.0254). EsoTL did not occur at maximal temperature less than 39 °C, measured by using esophageal temperature‐monitoring probe. Conclusions: Immediate discontinuation of ablation during pulmonary vein isolation remarkably decreased the incidence of EsoTLs, even when using STS.